2002
DOI: 10.1162/002081802760403748
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of Monetary Institutions

Abstract: In recent decades, countries have experimented with a variety of monetary institutions, including alternative exchange-rate arrangements and different levels of central bank independence. Political economists have analyzed the choice of these institutions, emphasizing their role in resolving both the time-inconsistency problem and dilemmas created by an open economy. This “first-generation” work, however, suffers from a central limitation: it studies exchange-rate regimes and central bank institutions in isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(109 citation statements)
references
References 67 publications
1
107
1
Order By: Relevance
“…Like any paradigm, it guides research by specifying what is known and unknown, what is fact and anomaly. Originally formulated in the context of trade policy, OEP has been extended to monetary and financial relations (Frieden 1988a(Frieden , 1991Bernhard et al 2003), foreign direct investment (Jensen 2006;Pinto and Pinto 2008), immigration (Leblang et al 2007), foreign aid (Milner 2006), regulation (Mattli and Woods 2009;Richards 1999), corporate governance (Gourevitch and Shinn 2005), and global governance (Kahler and Lake 2003). It now forms a comprehensive approach to explaining a large range of foreign economic policies.…”
Section: Open Economy Politicsmentioning
confidence: 99%
“…Like any paradigm, it guides research by specifying what is known and unknown, what is fact and anomaly. Originally formulated in the context of trade policy, OEP has been extended to monetary and financial relations (Frieden 1988a(Frieden , 1991Bernhard et al 2003), foreign direct investment (Jensen 2006;Pinto and Pinto 2008), immigration (Leblang et al 2007), foreign aid (Milner 2006), regulation (Mattli and Woods 2009;Richards 1999), corporate governance (Gourevitch and Shinn 2005), and global governance (Kahler and Lake 2003). It now forms a comprehensive approach to explaining a large range of foreign economic policies.…”
Section: Open Economy Politicsmentioning
confidence: 99%
“…The average equilibrium rate of inflation will be bk and the average equilibrium rate of output will be y * (given that f and e are mean zero). 5 The literature on monetary policy has considered a variety of mechanisms that might allow a politician to commit to a lower rate of inflation and as a result improve social welfare. One possibility is delegating policy to an independent central banker, who has a lower value of b than does the government.…”
Section: Transparencymentioning
confidence: 99%
“…In the case where a new government is trying to "build a reputation" for sound policy there may be uncertainty whether the government has merely adopted a "fair weather" strategy and will revert to a higher rate of inflation at some subsequent point. Recent contributions in game theory have suggested that it may, in many cases, be more relevant 5 The game is solved through backwards induction in the same manner as the standard Barro-Gordon game. The policy maker's preferred rate of inflation is solved for by first substituting equation 2, the supply curve, into her loss function (equation 1).…”
Section: Transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…Many other Latin American countries in fact now float their currencies against the dollar and other currencies (IMF 1997;Berg et al 2003). From this point of view, Latin America is now relatively less dollarized officially than it was in the late 1980s when many of its countries had currencies that were closely pegged to the dollar or adopted so-called intermediate mechanisms such as crawling pegs and bands (Jameson 1990; more generally on trends in adopting fixed versus floating exchange rates across developed and developing countries, see Bernhard et al 2002;Joshi 2003). In other words, the continent is stuck between the globalist and the imperialist regimes, even though many governments, if given a choice, would aspire to classic sovereignty.…”
Section: Latin Americamentioning
confidence: 99%